Peningkatan Bahan Ajar Berbasis ICT Pada Mata Pelajaran IPA-KIMIA SMP - Ade Onny Siagian (Mahesa Research Center, 2021)
This research was conducted in order to improve the teaching material in the form of an educational CD for class VII SMP with material on physical and chemical changes (chemical reactions). The stages of research and improvement carried out include: (1) needs analysis, (2) product improvement stage, (3) feasibility study and trial stage. Analysis of the needs of class VII students of SMPN 8 Jakarta with 39 respondents was carried out with the results that 100% of respondents had used computers at relatively frequent intervals (79.92%). More than half of the respondents (66.67%) stated that the seventh grade science (chemistry) subject was quite difficult. The product improvement stage begins with a literature study to create teaching material content, and the production of teaching materials in the form of interactive CDs. Educational materials are made using Macromedia Flash interactive programming facility which includes animation of chemical reaction applications, chemical reaction processes, and practice questions with multiple choice questions. The time required for the contents of this learning CD is 15-20 minutes. The feasibility test phase carried out by material experts, media and teachers showed that the learning CDs developed were suitable for practical use. Meanwhile, small and large group experiments with class IX students of SMPN 8 Jakarta and SMP Terpadu Widya Duta Jakarta gave very good interpretation results, so it can be concluded that CD is used for learning materials on physical and chemical changes.